2009
DOI: 10.1289/ehp.0800003
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Exposure to Environmental Pollutants and Body Mass Index during the First 3 Years of Life

Abstract: ObjectiveWe investigated the association between body mass index (BMI) standard deviation score (SDS) and prenatal exposure to hexachlorobenzene, dichlorodiphenyldichloroethylene (DDE), dioxin-like compounds, and polychlorinated biphenyls (PCBs).MethodsIn this prospective birth cohort study, we assessed a random sample of mother–infant pairs (n = 138) living in Flanders, Belgium, with follow-up until the children were 3 years of age. We measured body mass index as standard deviation scores (BMI SDS) of childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
148
6
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(171 citation statements)
references
References 38 publications
14
148
6
3
Order By: Relevance
“…Hence, global contamination by DDTs has caused serious concerns about possible adverse health effects to humans and animals (UNEP, 2001). Several previous studies have used DDT and its degradation products in human blood serum as biomarkers for health effects (Laden et al, 1999;Perry et al, 2005;Tiido et al, 2006;Qin et al, 2011), including possible negative effects of DDT on thyroid hormone function during pregnancy (Asawasinsopon et al, 2006;Chevrier et al, 2008;Langer et al, 2009), the effect of serum concentration of POPs in female during gestation (Meeker et al, 2009;Wang et al, 2009) as well as effect to their childhood (Verhulst et al, 2009). Other studies have suggested associations between organochlorine pesticides and type 2 diabetes as well as cardiovascular diseases (Codru et al, 2007;Rignell-Hydbom et al, 2009;Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, global contamination by DDTs has caused serious concerns about possible adverse health effects to humans and animals (UNEP, 2001). Several previous studies have used DDT and its degradation products in human blood serum as biomarkers for health effects (Laden et al, 1999;Perry et al, 2005;Tiido et al, 2006;Qin et al, 2011), including possible negative effects of DDT on thyroid hormone function during pregnancy (Asawasinsopon et al, 2006;Chevrier et al, 2008;Langer et al, 2009), the effect of serum concentration of POPs in female during gestation (Meeker et al, 2009;Wang et al, 2009) as well as effect to their childhood (Verhulst et al, 2009). Other studies have suggested associations between organochlorine pesticides and type 2 diabetes as well as cardiovascular diseases (Codru et al, 2007;Rignell-Hydbom et al, 2009;Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that hormones are key regulators in our body metabolism, body weight mechanisms and many pollutants affect our hormones [37]. For convenience, we spend time in temperature controlled rooms [38,39].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Cependant, dans un modèle de rongeur, une administration néonatale de diéthylstilbestrol qui induit une activation de la signalisation oestrogénique, entraîne aussi une obésité à l'âge adulte [22]. Une association positive entre les niveaux sériques de diéthylstilbes-trol mesurés à la naissance dans le sang du cordon et l'IMC (indice de masse corporelle) ultérieur des jeunes enfants a également été montrée [23]. Ces résultats soulignent l'importance des fenêtres d'exposition aux composés oestrogéniques dans la survenue des événements métaboliques futurs, possiblement parce que les oestrogènes ont des actions pléiotropes qui dépendent d'interactions contextuelles avec de nombreuses voies de signalisation comme la voie PPAR [24,25].…”
Section: Le Système Endocrinienunclassified